Analisis Deduktif Pergeseran Komunikasi Manusia-ke-Mesin terhadap Pemenuhan Kebutuhan Ekspresi Verbal dan Hirarki Maslow dalam Bimbingan Konseling - Mei Sarri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Generative artificial intelligence has shifted human communication patterns from human-to-human interaction to human-to-machine interaction. This change is reflected in the growing use of chatbots and AI companions as spaces for storytelling, seeking validation, and expressing verbal thoughts and emotions. This study aims to analyze this communication shift in relation to the fulfillment of verbal expression needs and Maslow’s hierarchy of needs in guidance and counseling practice. The study uses a deductive approach with a sequential explanatory mixed-methods design. Quantitative data are designed to be collected through daily communication tracking, AI conversation logs, a human-AI attachment scale, a Maslow need satisfaction scale, and computational linguistic analysis. Qualitative data are obtained through in-depth interviews with participants who show a high level of attachment to AI. The findings indicate that AI can provide a fast, responsive, personal, and nonjudgmental space for expression. However, the fulfillment of psychological needs through AI tends to be artificial because AI lacks emotional reciprocity, moral responsibility, and human presence as found in human counseling relationships. Intensive AI use also risks triggering emotional dependence, declining social skills, and weakened empathy in real relationships. The implication of this study emphasizes that AI should be positioned as a supporting tool in guidance and counseling services, not as a replacement for human counselors. Therefore, AI integration needs to be guided by a Pancasila-based ethical framework to protect the dignity, safety, and humanity of counselees.